MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
Chanchal Kumar Grade: 11
        

If the sum of first p terms of an A.P. is equal to the sum of the first q terms, then find the sum of the first (p + q) terms

6 years ago

Answers : (5)

vinay AskiitiansExpert-IITD
34 Points
										

Dear Chanchal,


equate sum of first p and q terms then write d multiplied by its coefficients on one side and a and its coefficients on the other and cancel (p-q) factor, collect all terms one side and you will get expression similar to that of  p+q term's sum which will give you value of sum as 0. 


 


We are all IITians and here to help you in your IIT JEE preparation.


Now you can win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.


Now you score 5+15 POINTS by uploading your Pic and Downloading the Askiitians Toolbar : Click here to download the toolbar.

6 years ago
rajan jha
49 Points
										

A/Q,


  p/2(2a+(p-1)d)=q/2(2a+(q-1)d)


=)p(2a+(p-1)d)=q(2a+(q-1)d)


=)2ap+p(p-1)d=2aq+q(q-1)d


=)2ap-2aq=d(q(q-1)-p(p-1))


 =)2a(p-q)=d(q^2-p^2+p-q)


after solving you get,  2a=-(p+q-1)d............................(1)


 


NOW


sum upto (p+q) terms = (p+q)/2(2a+(p+q-1)d)


                                 =(p+q)/2(2a-2a)                                  (from 1)


                                 =0.


best of luck.........................


like my answer?


 


 

6 years ago
vikas askiitian expert
510 Points
										

let the first term and common difference of AP is a and d....


sum of first q terms =sum of first p terms =k


q/2{2a+(q-1)d} = p/2{2a+(p-1)d} = k 


2a = 2k(q+p-1)/pq   and d=-2k/pq


now sum of first p+q terms =Sp+q= p+q/2 {2a +(p+q-1)d}


                                     =(p+q)/2{2k(p+q-1)/pq  - 2k(p+q-1)/pq }


                                    =0

6 years ago
AKASH GOYAL AskiitiansExpert-IITD
419 Points
										

one question to all of you solved this wat will be the sum when p-q=0 that is p=q this is the difficult case. why you neglected this case.

6 years ago
mycroft holmes
266 Points
										

The sum to n terms of an AP is given by the general expression 


 


We have 


 


Since p,q are assumed unequal, we have  so that the sum of (p+q)


terms is 0

6 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details